2014
DOI: 10.1007/s11302-014-9415-6
|View full text |Cite
|
Sign up to set email alerts
|

Vascular smooth muscle cells from small human omental arteries express P2X1 and P2X4 receptor subunits

Abstract: Stimulation of P2X receptors by ATP in vascular smooth muscle cells (VSMCs) is proposed to mediate vascular tone. However, understanding of P2X receptor-mediated actions in human blood vessels is limited, and therefore, the current work investigates the role of P2X receptors in freshly isolated small human gastro-omental arteries (HGOAs). Expression of P2X1 and P2X4 receptor subunit messenger RNA (mRNA) and protein was identified in individual HGOA VSMCs using RT-PCR and immunofluorescent analysis and using We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Immunofluorescence staining showed the localization of P2X 1 R, P2X 4 R, and P2X 7 R on the smooth muscle cells of intrarenal vessels in ANG II hypertensive rats; P2X 1 R localization is consistent with previous reports (10,30,40), whereas P2X 4 R distribution is predominantly endothelial (28). However, expression of P2X 7 R and P2X 4 R in the smooth muscle cells of small-and large-size vessels in both sham-operated and ANG II rats is a novel finding; previous studies have demonstrated a predominant endothelial localization, and scarce P2X 7 R in the smooth muscle of renal vessels and afferent arterioles (27,28).…”
Section: Renal Vascular Localization Of P2x Receptors and Protein Expressionsupporting
confidence: 91%
See 1 more Smart Citation
“…Immunofluorescence staining showed the localization of P2X 1 R, P2X 4 R, and P2X 7 R on the smooth muscle cells of intrarenal vessels in ANG II hypertensive rats; P2X 1 R localization is consistent with previous reports (10,30,40), whereas P2X 4 R distribution is predominantly endothelial (28). However, expression of P2X 7 R and P2X 4 R in the smooth muscle cells of small-and large-size vessels in both sham-operated and ANG II rats is a novel finding; previous studies have demonstrated a predominant endothelial localization, and scarce P2X 7 R in the smooth muscle of renal vessels and afferent arterioles (27,28).…”
Section: Renal Vascular Localization Of P2x Receptors and Protein Expressionsupporting
confidence: 91%
“…In this context, expression of P2X 1 R in the smooth muscle cells of kidney vessels in sham-operated and hypertensive rats, as previously described (10,30,40), may contribute to the vasodilatory responses to receptor blockade as observed in the hypertensive group in this study. In addition, the effects on glomerular hemodynamics in sham-operated rats suggest a role for this receptor in regulating glomerular hemodynamics during normal physiological conditions.…”
Section: Glomerular Microcirculation Under P2x 1 and P2xsupporting
confidence: 74%
“…The contractile actions of ATP released from perivascular sympathetic nerves are mediated principally via P2X1 receptors, confirmed by the use of P2X1 genetic knockout mice. However, in some vessels (eg, human omental arteries 71 and rat basilar arteries 72 ), smooth muscle cells also express P2X4 receptors. P2X5 and P2X1 receptors are expressed by rat small mesenteric arteries, 73 and P2X1/4 heteromeric receptors mediate constriction of rat cerebral arteries.…”
Section: Perivascular Nervesmentioning
confidence: 99%
“…Stimulation of P2X1R mediated vasoconstriction in vascular smooth muscle cells (VSMCs) from human gastro-omental arteries [87]. In addition, P2X1R is activated by neurally released ATP mediated Ca 2+ entering the smooth muscle cells, thus inducing the sympathetic neurogenic contraction.…”
Section: P2x1 Receptors Mediate Vasoconstriction and Renal Injurymentioning
confidence: 99%